Ruhuna benchmark basin activities: proceedings of the inaugural meeting held at Peacock Beach Hotel, Hambantota, Sri Lanka, 15 June 2001 - Hemakumara, M.; Barker, Randolph; Droogers, Peter (International Water Management Institute, 2001)
This paper presents a Benchmark Basin initiative which was proposed in IWMI's Strategic Plan 2001-2005 as an approach to understand and beneficially influence water resources development in selected basins in a variety of agro-ecological zones.The initial task represented by this workshop is to conduct a dialogue among partners and stakeholders in the Ruhuna Basin,Sri Lanka. A major objective is to identify these issues and research and also development activities considered to be of highest priority to partners and stakeholders.